2019
DOI: 10.7554/elife.45210
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial riboswitch class for the thiamin precursor HMP-PP employs a terminator-embedded aptamer

Abstract: We recently implemented a bioinformatics pipeline that can uncover novel, but rare, riboswitch candidates as well as other noncoding RNA structures in bacteria. A prominent candidate revealed by our initial search efforts was called the ‘thiS motif’ because of its frequent association with a gene coding for the ThiS protein, which delivers sulfur to form the thiazole moiety of the thiamin precursor HET-P. In the current report, we describe biochemical and genetic data demonstrating that thiS motif RNAs functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…4C). This gene expression "halo" pattern has been observed for other riboswitch classes subjected to similar agar diffusion assays (Kim et al 2015;Atilho et al 2019a).…”
Section: Nicotinic Acid Biosynthesis Is Important For Gene Repressionsupporting
confidence: 71%
See 1 more Smart Citation
“…4C). This gene expression "halo" pattern has been observed for other riboswitch classes subjected to similar agar diffusion assays (Kim et al 2015;Atilho et al 2019a).…”
Section: Nicotinic Acid Biosynthesis Is Important For Gene Repressionsupporting
confidence: 71%
“…Even when nadA motif constructs carry both domains, it is possible that the second aptamer might be rendered inoperable because they are thermodynamically trapped in an inactive state. This is the case for some riboswitches in which the expression platform precludes ligand binding because this mutually exclusive structure is more stable than the ligandbinding aptamer conformation (Wickiser et al 2005a;Atilho et al 2019a). In some instances, in-line probing results indicate that domain 2 indeed is poorly formed.…”
Section: Resultsmentioning
confidence: 99%
“…This thiS motif is conserved in actinobacteria, firmicutes and metagenomic DNA datasets. A deeper characterization of this RS unveiled that the aptamer selectively binds HMP, an intermediate in the biosynthesis of thiamine, instead of TPP [35]. An in silico investigation suggests that this thiS motif is not present in Neisseria.…”
Section: Discussionmentioning
confidence: 93%
“…Despite these clues, ligand binding assays initially failed to reveal the natural ligand for this riboswitch class. However, the use of riboswitch reporter-fusion constructs and bacterial strains with knockouts of genes in the TPP biosynthetic pathway revealed that another intermediate, HMP-PP, was the ligand (Stav et al 2019;Atilho et al 2019). The riboswitch senses the build-up of HMP-PP to activate the expression of genes involved in producing HET-P, which together form the final coenzyme product.…”
Section: This Motif Rnas: Riboswitches For Hmp-ppmentioning
confidence: 99%
“…These latter riboswitches, for glycine and HMP-PP, only resisted initial attempts at biochemical validation due to their unusual architectures Stav et al 2019;Atilho et al 2019). In general, amino acid and coenzyme biosynthesis pathways have been extensively studied, whereas certain signaling networks and metal ion homeostasis processes represent complex topics of study that are still being explored.…”
Section: Perplexing Gene Associationsmentioning
confidence: 99%